2017
DOI: 10.1016/j.jams.2017.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acupuncture on 1-chloro-2,4-dinitrochlorobenzene-induced Allergic Contact Dermatitis in Mice

Abstract: Allergic contact dermatitis (ACD) is a chronic inflammatory skin disease. Topical corticosteroids are the first-line therapy for ACD despite their significant adverse effects. Acupuncture has been widely used in the treatment of various skin diseases, but its underlying mechanism remains unrevealed. In this study, we investigated the characteristics of acupuncture treatment based on effectiveness and mechanism. BALB/c mice received 1-chloro-2,4-dinitrobenzene (DNCB) application to build AD-like model. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The robust capability of Au/PATP/Hemin nanoprobe for in vivo ROS detection were evaluated in another mouse model of allergic dermatitis, a chronic inflammatory skin disease (Figure A). As shown in Figure B, 2,4-dinitrochlorobenzene was used to induce allergic contact dermatitis in nude mice; hematoxylin-eosin (H&E) stain showed severe edema, hyperplasia, and massive infiltration of inflammatory cells in the epidermis and dermis of mice skins, confirming successful establishment of the allergic dermatitis model. Au/PATP/Hemin nanoprobe was then dropped onto the inflammatory sites of mice skins, and SERS spectra were monitored at the time points of 0, 1, 2, 3, and 4 h. As shown in Figure C,D, Au/PATP/Hemin-dropped inflammatory skin elicited strong SERS signals of DMAB at 1142, 1386, and 1432 cm –1 , and the ratiometric peak intensity of I 1142 / I 1077 dramatically increased over time, indicating a gradually increasing ROS level during the inflammatory process.…”
Section: Results and Discussionmentioning
confidence: 83%
“…The robust capability of Au/PATP/Hemin nanoprobe for in vivo ROS detection were evaluated in another mouse model of allergic dermatitis, a chronic inflammatory skin disease (Figure A). As shown in Figure B, 2,4-dinitrochlorobenzene was used to induce allergic contact dermatitis in nude mice; hematoxylin-eosin (H&E) stain showed severe edema, hyperplasia, and massive infiltration of inflammatory cells in the epidermis and dermis of mice skins, confirming successful establishment of the allergic dermatitis model. Au/PATP/Hemin nanoprobe was then dropped onto the inflammatory sites of mice skins, and SERS spectra were monitored at the time points of 0, 1, 2, 3, and 4 h. As shown in Figure C,D, Au/PATP/Hemin-dropped inflammatory skin elicited strong SERS signals of DMAB at 1142, 1386, and 1432 cm –1 , and the ratiometric peak intensity of I 1142 / I 1077 dramatically increased over time, indicating a gradually increasing ROS level during the inflammatory process.…”
Section: Results and Discussionmentioning
confidence: 83%
“…Conventional treatment of ACD and AD often involves the topical or systemic use of immunosuppressants such as corticosteroids, cyclosporine, and tacrolimus. However, these drugs can have side effects with prolonged use [25,26]. Because peptide drugs are composed of endogenous amino acids, they are considered to have high potential therapeutic activity and low toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…47 It has been shown that CD4 + T cells are involved in the disease process and among various Th cell subsets, Th1 cells are considered as the main cellular players in inflammation, 48 although other cell types, including Th2 and Th17 cells, may also be involved in disease development. 49,50 In recent years, growing attention has been paid to the role of Th9 cells in ACD and current evidence indicates the potential relevance of these cells to disease pathogenesis.…”
Section: Allergic Contact Dermatitis (Acd)mentioning
confidence: 99%